2022
DOI: 10.1136/bmjopen-2021-060490
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experiences of being treated for acute illness at home as an alternative to hospital admission: a qualitative study in Denmark

Abstract: ObjectiveWe aimed to investigate the experiences of Danish patients treated at home for an acute illness instead of being hospitalised.DesignThis study had a qualitative design inspired by the methodology of interpretive description. Data were collected through semistructured interviews.SettingHome treatment was conducted by a team of nurses (n=10–15) supported by physiotherapists and physicians, all affiliated with an emergency department, located in the capital region of Denmark. Interviews were conducted be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The quality of HaH service was studied from the perspective of patients and caregivers in 18 studies and shown to provide hospital‐level treatment at home and met patients' needs (Bove et al, 2022; Dismore et al, 2019; Facultad & Lee, 2019; Lai et al, 2021; Leff et al, 2008; Udesen et al, 2021; Utens et al, 2014; Vaartio‐Rajalin et al, 2021; Wang et al, 2012). Applying the objective outcomes, such as 30‐day all‐cause hospital readmissions (Federman et al, 2018), length of hospital stay (Samaranayake et al, 2020), patients and caregivers reported that they perceived better health outcomes (Dismore et al, 2019; Federman et al, 2018; Herranz et al, 2022; Ko et al, 2022; Levine, Pian, et al, 2021; Samaranayake et al, 2020; Wang et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The quality of HaH service was studied from the perspective of patients and caregivers in 18 studies and shown to provide hospital‐level treatment at home and met patients' needs (Bove et al, 2022; Dismore et al, 2019; Facultad & Lee, 2019; Lai et al, 2021; Leff et al, 2008; Udesen et al, 2021; Utens et al, 2014; Vaartio‐Rajalin et al, 2021; Wang et al, 2012). Applying the objective outcomes, such as 30‐day all‐cause hospital readmissions (Federman et al, 2018), length of hospital stay (Samaranayake et al, 2020), patients and caregivers reported that they perceived better health outcomes (Dismore et al, 2019; Federman et al, 2018; Herranz et al, 2022; Ko et al, 2022; Levine, Pian, et al, 2021; Samaranayake et al, 2020; Wang et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Patients' and caregivers' experienced interactions with HaH services have been found to exert a significant influence on their preferences when selecting such services. Within the realm of HaH service utilisation, eight studies consistently highlight the paramount importance of feeling secure and receiving safe care at home as a fundamental consideration (Bove et al, 2022; Chua et al, 2022b; Facultad & Lee, 2019; Leff et al, 2006; Makela et al, 2020; Samaranayake et al, 2020; Udesen et al, 2021; Wang et al, 2012). Addressing the location of care, the convenience and comfort afforded by HaH services were frequently highlighted as advantages (Lemelin et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations